The cutting edge in the blunt space: an anthropological construct of auxiliary nurse midwives’ social world in the community - Avanish Kumar; Meerambika Mahapatro (Healthcare in Low-resource Settings, 2013)
Auxiliary nurse midwives (ANMs) are the most peripheral health providers and manage the rural health sub-centre in a community. They mediate directly between the community and the health system for the management of Maternal and Child Health Programme in India. The purpose of this study was to find out the role of cultural factors, such as ANMs’ caste, age, marital status, being non-resident in the working village and other social factors regarding their acceptance in the community. The study is exploratory and qualitative. The area of study was a multi-caste remote village, Mavaibhachan, in Kanpur Dehat district of Uttar Pradesh, India. Data were collected through in-depth interviews and fieldwork notes taken during and immediately after the interviews with ANMs, and thematically analyzed. Our results show that if ANMs belong to a different caste group, do not live in the working village and are relatively younger, they are socially insecure and stressed and the community hardly accepts them. Despite direct interface with the community, their social status and lowest position in the health system is reflected in acceptability and recognition. The position of ANMs needs to be strengthened, within society and the health system. In order to make public health services effective and efficient the health system has to reduce stratification based on role and status.